The influence of emotional intelligence on internships in higher Education - Ramírez-Hurtado, José M.; González-Zamora, María del Mar; Vazquez-Cano, Esteban (Revista Complutense de Educación, 2022)
Internships are temporary jobs that provide real-time work and experience for students. They are well appreciated not only by students, but also by academics and companies. Despite the importance and growth of internship programmes in higher education, little is known about the influence of Emotional Intelligence (EI) on them. We attempt to address this gap relating the effect of EI on internships, employability and satisfaction with these internships. For this purpose, a structural equation model was applied to a sample of 240 students from two Spanish universities. Our results indicate that EI directly influences doing university students’ internships. The results also enable us to state that EI has an indirect influence on the improvement of employability and the students’ level of satisfaction with the internships. These findings can assist universities, academics, faculties and host companies for the improvement of the design of internship programmes in higher education.